2017
DOI: 10.3389/fpls.2017.00180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Toxic Boron Concentration on Protein Profiles in Roots of Two Citrus Species Differing in Boron-Tolerance Revealed by a 2-DE Based MS Approach

Abstract: Citrus are sensitive to boron (B)-toxicity. In China, B-toxicity occurs in some citrus orchards. So far, limited data are available on B-toxicity-responsive proteins in higher plants. Thirteen-week-old seedlings of “Sour pummelo” (Citrus grandis) and “Xuegan” (Citrus sinensis) was fertilized every other day until dripping with nutrient solution containing 10 μM (control) or 400 μM (B-toxicity) H3BO3 for 15 weeks. The typical B-toxic symptom only occurred in 400 μM B-treated C. grandis leaves, and that B-toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 70 publications
(96 reference statements)
0
17
0
Order By: Relevance
“…The authors demonstrated that 'Clementine' mandarin and 'Navelina' orange plants grafted on 'sour orange' rootstock are more sensitive to high B compared to those grafted on 'Swingle citrumelo' due to lower B uptake, which resulted in decreased B accumulation in leaves (Papadakis et al 2004a, b). Recently, a proteomic approach carried out in roots of C. sinensis and C. grandis revealed that under high B concentration proteins involved in many cellular processes, including B transport and accumulation, are differentially expressed in the two species and play a key role in conferring B-tolerance to C. sinensis (Sang et al 2017). Therefore, understanding the intimal mechanism of B transport within plant and the mechanisms which allow tolerant genotype to cope better with higher B concentration is of crucial importance to drive, for example, future breeding programs aimed to select tolerant genotypes.…”
Section: Roles Of Boron Transporters and Efflux Pumps In B Tolerancementioning
confidence: 99%
“…The authors demonstrated that 'Clementine' mandarin and 'Navelina' orange plants grafted on 'sour orange' rootstock are more sensitive to high B compared to those grafted on 'Swingle citrumelo' due to lower B uptake, which resulted in decreased B accumulation in leaves (Papadakis et al 2004a, b). Recently, a proteomic approach carried out in roots of C. sinensis and C. grandis revealed that under high B concentration proteins involved in many cellular processes, including B transport and accumulation, are differentially expressed in the two species and play a key role in conferring B-tolerance to C. sinensis (Sang et al 2017). Therefore, understanding the intimal mechanism of B transport within plant and the mechanisms which allow tolerant genotype to cope better with higher B concentration is of crucial importance to drive, for example, future breeding programs aimed to select tolerant genotypes.…”
Section: Roles Of Boron Transporters and Efflux Pumps In B Tolerancementioning
confidence: 99%
“…Proteins were extracted using a phenol extraction procedure [80] and their concentration was measured as described by Bradford [81]. 2-DE was performed according to Sang et al [82]. Stained gels were scanned with an Epson Scanner (Seiko Epson Corporation, Japan) at a resolution of 300 dpi.…”
Section: Leaf Protein Extraction 2-de and Image Analysismentioning
confidence: 99%
“…Proteins were independently extracted thrice from pH 2.5-, 3- and 6-treated samples using a phenol extraction procedure as described previously [ 32 ] and their concentrations were determined according to Bradford [ 33 ]. Both 2-DE and image analysis were performed as described by Sang et al [ 34 , 35 ] and Yang et al [ 36 ]. Background subtraction, Gaussian fitting, gel alignment, spot detection, matching and normalization were made with PDQuest version 8.0.1 (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%